KEWAJIBAN SUAMI DALAM MEMBERI NAFKAH - Yulianti Yulianti (Syariah Darussalam : Jurnal Ilmiah Kesyariahan dan Sosial Masyarakat, 2021)
Islam has regulated everything in married life. A husband or a wife has their respective rights and obligations, which if these rights and obligations are fulfilled, a harmonious and happy household will be achieved, and vice versa if these rights and obligations are not carried out properly it can result in the termination of the marriage. One of the obligations of a husband is to provide a living for his wife, and maintenance is the right of a wife. Subsistence is everything that has a value of benefit or material value that a husband can give to his wife and children as a responsibility to meet the needs of the people he bears. The husband occupies the highest position in a marriage, namely as the head of the family in his family so that it has become his obligation to meet all the needs of his wife and children, both housing, clothing, and food. Syari’ah obliges the husband to provide for his wife after a marriage contract is held because of the continuity of having fun as a wife is obliged to obey her husband, manage all things in the household, and educate her children. However, the provision of a living must first see the limits of a husband's ability.